2020
DOI: 10.1167/tvst.9.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Determinants of Eyecare Utilization and Eyeglass Affordability Among Individuals With Visual Impairment in a Multi-Ethnic Population-Based Study in Singapore

Abstract: Rates and determinants of eyecare utilization and eyeglass affordability among individuals with visual impairment in a multi-ethnic population-based study in Singapore. Trans Vis Sci Tech. 2020;9(5):11, https://doi.org/10.1167/tvst.9.5.11Purpose: The purpose of this study was to determine the rates of, and factors associated with, eyecare utilization and spectacle affordability among Singaporeans with vision impairment (VI). Methods:We included adults with VI from their second visit of the Singapore Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
5
1
Order By: Relevance
“…This may explain why greater effort was made by these patients to ensure the maintenance of their vision. This is in contrast to a Singaporean study, which reported that people with visual impairment had low eye care utilization 23 ; the discrepancy is likely attributable to different definitions for visual disability and visual impairment in their study. Although lack of eye care utilization can lead to visual impairment, 24 our study adds to existing knowledge in 2 ways.…”
Section: Discussioncontrasting
confidence: 99%
“…This may explain why greater effort was made by these patients to ensure the maintenance of their vision. This is in contrast to a Singaporean study, which reported that people with visual impairment had low eye care utilization 23 ; the discrepancy is likely attributable to different definitions for visual disability and visual impairment in their study. Although lack of eye care utilization can lead to visual impairment, 24 our study adds to existing knowledge in 2 ways.…”
Section: Discussioncontrasting
confidence: 99%
“…[10] Surprisingly, our study found that people with chronic diseases were less likely to use eye care services, however, others found that chronic diseases are associated with ECU. [23,35] A recent study found that understanding of health and disease is a key determinant of seeking healthcare among persons with chronic conditions in Malawi. [36]…”
Section: Discussionmentioning
confidence: 99%
“…[10] Surprisingly, our study found that people with chronic diseases were less likely to use eye care services, however, others found that chronic diseases are associated with ECU. [23,35] A recent study found that understanding of health and disease is a key determinant of seeking healthcare among persons with chronic conditions in Malawi. [36] Regarding residence, our investigation revealed that people from the urban areas utilize eye care services more than their rural counterparts comparable to previous studies [23] The rural urban disparity can be explained by less available ophthalmic human resources in rural areas.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Routine eye examinations are important for the timely detection and management of vision issues. As the major causes of Visual Impairment (VI) and blindness are treatable, appropriate use of eye care services, such as regular eye examinations, is a key factor in optimizing national eye health [10].…”
Section: Discussionmentioning
confidence: 99%